Study of Physical Properties of Rocks and Acid Mine Drainage Potential at Banko Barat Tanjung Enim - Siti Sailah (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
One of the factors that generate acid mine drainage (AMD) is the presence of sulphide minerals in rocks because sulphide minerals will have oxidation with oxigen and water to generate AMD. Learning sulphide minerals in rocks can not be separated from the rocks themselves. Present paper is an attempt to study how the physical properties of rocks are and their influences in generating acid mine drainage. At Banko barat, especially at PIT 3 timur, the lithology of rocks is complex. It is assumed that the complexity of rocks will influence the complexity of formation of acid mine drainage. Thus by knowing the characteristics of each rock it is expected to be useful in identification of which rocks require special attention in the mine planning process.